2016
DOI: 10.1186/s12884-016-0960-6
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of use of supervised delivery care under Ghana’s fee exemption policy for maternal healthcare: the case of the Central Region

Abstract: BackgroundImproving access to supervised and emergency obstetric care resources through fee reduction/exemption maternity care initiatives has been touted as one major strategy to avoiding preventable maternal deaths. Evaluations on the effect of Ghana’s fee exemption policy for maternal healthcare have largely focused on how it has influenced health outcomes and patterns of use of supervised care with little attention to understanding the main factors influencing use. This study therefore sought to explore th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Findings of this study nonetheless, validate some literature on Ghana [20] and other African countries [21, 22] where client-centered healthcare system is advocated through bottom-up community engagement to promote acceptability and utilization of safer healthcare services. Previous studies have blamed the lack of clients’ confidence in formal healthcare systems on low level of engagement of communities in the entire value chain of healthcare delivery [18, 20].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Findings of this study nonetheless, validate some literature on Ghana [20] and other African countries [21, 22] where client-centered healthcare system is advocated through bottom-up community engagement to promote acceptability and utilization of safer healthcare services. Previous studies have blamed the lack of clients’ confidence in formal healthcare systems on low level of engagement of communities in the entire value chain of healthcare delivery [18, 20].…”
Section: Discussionsupporting
confidence: 80%
“…Engagement of clients in health service delivery is more likely to enhance knowledge levels of mothers on importance of antenatal and postnatal care services as alluded by Asante-Sarpong et al [20]. Similarly, a study by Agbozo et al [16] underscored the positive association between a community-based health programme on child welfare, growth monitoring and mothers’ satisfaction level with service quality in a study on Ghana.…”
Section: Discussionmentioning
confidence: 95%
“…"Nearly nine in ten women in urban areas (88%) deliver in a health facility, compared to 53 percent of their rural counterparts" (MICS, 2011) [8]. These findings are confirmed by the findings of Asante-Sarpong et al, (2016) which revealed; "Mothers living in urban areas are 3.79 times more likely to use skilled delivery services under the NHIS policy than those living in rural areas" [9].…”
Section: Introductionmentioning
confidence: 88%
“…Research findings by Asante-Sarpong et al, (2016) revealed that delivery service use under the free maternal healthcare policy is relatively low (65%) when compared with nearly universal awareness (97.3%) of Ghanaian pregnant women about the policy. However, "the likelihood of using delivery services under the policy is higher for mothers who are aware and has full knowledge of the total benefit package of the policy" [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that 99% of all maternal-related deaths occur in low- and middle-income countries, of which most (66%) are located in sub-Saharan Africa (SSA) [5–8]. Maternal mortality in SSA is 1 in 39 live births, whereas it is 1 in 3800 live births in high-income countries [9, 10], 1 in every 130 live births in Oceania, and 1 in every 160 live births Southern Asia [5–8]. Therefore, increasing access to quality maternal healthcare services in SSA has been a global priority since the inception of the Millennium Development Goals to date.…”
Section: Introductionmentioning
confidence: 99%